Clonal bamboo production based on in vitro culture (Bioscience Journal, 2020)
Bamboo species are an alternative for the composition of forest plantations. However, their potential has not been explored due to the hard time in producing large-scale clonal plants. Thus, the aim this work was to evaluate the in vitro establishment, bud multiplication and ex vitro rooting of Bambusa vulgaris. The first experiment tested different systemic and contact fungicide solutions, based on exposure time, during the establishment phase. Established explants were subjected to evaluation of residual fungicide effect on subcultures during the multiplication and elongation phases. The second experiment evaluated the influence of activated carbon on ex vitro survival and on adventitious rooting. Explant immersion in liquid culture medium added with 1.0 mL of fungicide for 120 hours has favored the in vitro establishment and reduced fungal contamination. On the other hand, it favored the shoot emission of shoots per explant during the multiplication phase. Both rooting induction culture medium and mini-incubator system use were effective in enabling adventitious root formation. The presence of activated carbon in the rooting induction culture medium resulted in a higher clonal plant survival rate.